2019
DOI: 10.3389/fphys.2019.00807
|View full text |Cite
|
Sign up to set email alerts
|

Static Metabolic Bubbles as Precursors of Vascular Gas Emboli During Divers’ Decompression: A Hypothesis Explaining Bubbling Variability

Abstract: Introduction The risk for decompression sickness (DCS) after hyperbaric exposures (such as SCUBA diving) has been linked to the presence and quantity of vascular gas emboli (VGE) after surfacing from the dive. These VGE can be semi-quantified by ultrasound Doppler and quantified via precordial echocardiography. However, for an identical dive, VGE monitoring of divers shows variations related to individual susceptibility, and, for a same diver, dive-to-dive variations which may be influenced by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…With supersaturated N 2 in tissues, even VGE formation is possible due to very rapid ascents from deep breath-hold dives (Foster et al 2016). Recently, preexisting populations of gas bubbles populated and stabilized by tissue metabolism have been linked to the formation of nucleation sites that could relate to the VGE detected post-dive (Imbert et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With supersaturated N 2 in tissues, even VGE formation is possible due to very rapid ascents from deep breath-hold dives (Foster et al 2016). Recently, preexisting populations of gas bubbles populated and stabilized by tissue metabolism have been linked to the formation of nucleation sites that could relate to the VGE detected post-dive (Imbert et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even more, many modifications to the decompression schedule, implemented by technical divers, such as gradient factors or deep stops, have not been validated by any human dive trials (Doolette and Mitchell 2013 ). Although several thousand dives are reported to have been conducted safely in the field, one cannot assume a similar degree of confidence without proper data gathering (Imbert et al 2019 ; Buzzacott et al 2014 ), It has indeed already been demonstrated that technical diving in open circuit up to 70 m is associated with a high decompression stress (Ljubkovic et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, regardless of the decompression algorithm used, detectable VGE may be measured after recreational, technical and (to a lesser degree) professional diving (Dunford et al 2002 ). The amount of VGE is considered to be statistically related to the risk of DCS after a dive (Imbert et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that low plasma surface tension can be attributed to bubble formation [ 32 ]. On the other hand, the ingestion of normal saline solution prior to hypobaric exposure can temporarily raise surface tension, contributing to the protection against altitude DCS [ 33 , 34 ]. Another study suggested that pre-hydration can attenuate dehydration resulting from higher fluid retention and prevent hypovolemia during diving [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this study, the circulating vascular bubbles on the right and left subclavian veins and precordial region were measured only immediately after the dive and once again 30 min later, although it is recommended that bubble measurements should be conducted during the first 120 min following decompression with intervals being no longer than 20 min [ 31 ]. Secondly, although previous studies suggest that various factors such as age, diet or nutrition, fitness, and physical activities can affect the variability in vascular gas emboli or small metabolic bubble populations [ 32 , 33 , 34 , 35 ], we controlled only diet and physical activities during the experiment. Thirdly, water was used for pre-hydration in this study, but some studies have used other solutions, such as a saline-glucose solution.…”
Section: Discussionmentioning
confidence: 99%